MOF@SiO2 core-shell composites as stationary phase in high performance liquid chromatography - Ehrling, Sebastian; Kutzscher, Christel; Freund, Pascal; Mueller, Philipp; Senkovska, Irena; Kaskel, Stefan (Microporous and Mesoporous Materials, 2018)
Mesoporous silica spheres were functionalized with microporous metal-organic frameworks (MOFs), namely MIL-101(Fe)_NH2 (Fe3(O)(BDC_NH2)3(OH)(H2O)2, BDC = benzene-1,4–dicarboxylate) and UiO-67 (Zr6O4(OH)4(BPDC)6, BPDC = 4,4′-biphenyldicarboxylate) to produce core-shell particles for application as stationary phase in high performance liquid chromatography (HPLC) columns using a layer-by-layer method. The composites were studied for application as stationary phase in normal phase HPLC for separation of C8-isomers, dichlorobenzene isomers, styrene and ethylbenzene. Both silica/MOF composites show the highest affinity towards the ortho substituted analytes, indicating that the selectivity is dominated by the polarity of the analytes. Moreover, the UiO-67@SiO2 composite shows high separation efficiency in the separation of dimethyl phthalate and diethyl phthalate, since the number of theoretical plates per meter is very high (37570 m−1).
CRIS-Team Scopus Importer:2022-04-14
Keywords: Core-shell particles; HPLC; Metal-organic framework; Polarity; Stationary phase